Analysis of Usage of E-Sports Commentator Register in Youtube Account Mpl Id S8 Playoff - Akbar Adi Prasetyo; Fida Pangesti; Fauzan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research aims to describe the form and meaning of the E-Sports commentator register on the social media youtube MPL ID S8 Playoffs. To solve the problem, this study uses a sociolinguistic approach. Research data is a list of e-sports commentators containing registers, with YouTube video data sources Mobile Legend Bang-bang Indonesia and informants. The data is networked using the log-in and interview methods. The data that has been collected is then analyzed using alternative techniques with reference to the problems that have been formulated. Research results show that the register on E-Sports commentators can be (1) words formed through the process of affixing, reduplication, and abbreviation, as well as (2) phrases that include nominals, verbs, adjectives, and numerals. Furthermore, the meaning formed in the E-Sports commentator registry is divided into two groups of meaning, namely the limited circle registry and the open circular registry. The limited circular register has a narrow meaning coverage with a limited number. On the contrary, the open circle register has an extensive meaning cover with a number that tends to expand.